(3Gdeaghe hGdESJQGJLjIs - (3UdGM(B, (3GdTJhGfjs ((3GdEScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2000)
(3JLO aj gPG GdcJGH (B: (3Gdeaghe GdJShjbj ,GdEOGQI GdJShjbjI ,HMhK GdJShjb ,JUee GdHMhK ,WQb LeY GdHjGfGJ ,Gdgjcd GdJfXjej GdJShjbj ,GdShb ,Shb GdSdY GdESJgdGcjI ,Shb GdSdY GdUfGYjI ,JNWjW GdSdYI,ESJbUGA GdShb ,GdefTCJ GdJShjbjI ENJjGQ eSGdc GdJhRjY , OhQ GdEYdGf, EOGQI GdbhI GdYGedI aj GdHjY , GdeSDhdjI GdELJeGYjIs
(3HjHdjhZQGajG (B:(3U(B.413s
Keywords: (3GdJShjbs